Feed management practices and performance characteristics in finishing feedlot of beef cattle in the south and southeast of Pará (Research, Society and Development, 2023)
The aim of this study was to characterize the feedlot system in the south and southeast of Pará state. Nine professionals completed the survey on an electronic survey consisting of 65 questions. Corn was the main source of grain used in finishing diets, most of the Flint type. Fine grinding and coarse grinding were the main grain processing methods adopted. The most adopted level of inclusion of concentrate and roughage was from 71 to 81% and from 20 to 40% respectively. More than 50% of respondents adopted an adaptation period of more than 14 days and an initial roughage level of diets from 35 to 50% of dry matter. Most cattle fed in the feedlots surveyed are Nellore intact males. Most animals were fed for up to 100 days and left the feedlot weighing more than 550 kg of BW. The finishing diets adopted in feedlots located in the south and southeast region of Pará state presented a lower level of inclusion of concentrated and higher inclusion of roughage than the national average. Processing methods that increase the digestibility of Flint-type corn starch are still rarely used. Nellore intact males are slaughtered heavier than the national average. The feedlot system in the south and southeast of Pará has accompanied the development of the beef industry in Brazil.